War of the Schools and psychology: Colombia 1876 - Oviedo, Gilberto; Universidad de los Andes (Pontificia Universidad Javeriana, 2014)
The war of the schools was a political-military dispute the spiritual formation of the Colombian population. The liberal radicalism replaced religious education in 1872, inherited from Spain, by pestalozzian´s pedagogy. Conservatism reacted to restore the soul and spirituality of scholastic education run by the Church. Political ideas about the human mind was a slogan of battle and your war scenario education. The War of 1876 demonstrated the popular predilection for religious discourse and consideration of the psyche as a supernatural fact understandable in the light of faith. The terms of the debate are a valuable conceptual piece, reflecting the Colombian approach to psychology in the nineteenth century.